The Anti-depression Effect of Angelicae Sinensis Radix Is Related to the Pharmacological Activity of Modulating the Hematological Anomalies - Gong, Wenxia; Zhu, Shiwei; Chen, Congcong; Yin, Qicai; Li, Xiao; Du, Guanhua; Zhou, Yuzhi; Qin, Xuemei (Frontiers in Pharmacology, 2019)
Angelicae Sinensis Radix (AS), a well-known traditional Chinese medicine (TCM) herb, has been wildly used for replenishing the blood and promoting circulation in Asia for thousands of years. It has been confirmed that AS also possessed the pharmacological activity of anti-depression. At the same time, recent studies suggested that depression is associated with anemia, and depression could be ameliorated via modulating the blood system. However, it was still unknown whether the anti-depression effect of AS is related to its pharmacological activity of modulating the blood system. In the current study, hematological examination and metabonomics technique were performed to explore potential anti-depression mechanisms of AS releated to the function of modulating the blood system in chronic unpredictable mild stress (CUMS) model. The result demonstrated that AS could significantly improve the CUMS-induced depressive symptom, the haematological anomalies, and the hypoxia symptom. The analysis of metabonomics demonstrated that 26 potential biomarkers in depression could been regulated by the administration of AS. Among them, 8 biomarkers participate in the metabolic pathways of amino acid, sphingolipid, and energy metabolism could also be regulated in anemia model by the administration of AS as reported in previous literatures. Further results proved that AS modulated energy metabolism in depression through the inhibition of the expression of pyruvate dehydrogenase lipoamide kinase isozyme 1 (PDK-1) and lactate dehydrogenase A (LDHA). These results suggested that modulation of the blood system was involved in the anti-depression effect of AS. The mechanism may be associated with the promotion of body's energy metabolism, the stabilizing of cell membrane, the promotion of serum protein synthesis, and the enhancing of immunity.